Evaluation, Gap Analysis, and Potential Expansion of the Finnish Marine Protected Area Network - Virtanen, Elina A.; Viitasalo, Markku; Lappalainen, Juho; Moilanen, Atte (Frontiers in Marine Science, 2018)
Marine Protected Areas (MPAs) are essential for safeguarding marine biodiversity. Various international and regional agreements require that nations designate sufficient marine areas under protection. Assessing the functionality and coherence of MPA networks is challenging, unless extensive data on species and habitats is available. We evaluated the efficiency of the Finnish MPA network by utilizing a unique dataset of ∼140,000 samples, recently collected by the Finnish Inventory Programme for the Underwater Marine Environment, VELMU. Using the quantitative conservation planning and the spatial prioritization method Zonation, we identified sites of high biodiversity and developed a balanced ranking of marine conservation values. Only 27% of the ecologically most valuable features were covered by the current MPA network. Based on the analyses, a set of expansion sites were identified that efficiently complement the ecological and geographical gaps in the current MPA network. Increasing protected sea area by just one percent point, would double the mean conservation cover, and specifically increase the protection levels of habitat types based on IUCN Red List of Ecosystems, key species, threatened species and fish reproduction areas. We also discovered that a large part of ecologically valuable species, such as many brown and red algae, blue mussels and eelgrass, exist in the underwater parts of rocky islands and sandy shores. These areas do not belong to the present (Finnish) interpretation of the habitats (e.g., reefs and underwater sandbanks) listed in the EU Habitats Directive. Neglecting these environments may lead to lack of protection of functionally important biodiversity. We emphasize that, in addition to establishing MPAs, also ecosystem-based marine spatial planning is needed to safeguard the integrity of marine biodiversity in the northern Baltic Sea. The spatial prioritization maps produced in this study are essentially environmental value maps which can also be used in impact avoidance, such as siting of wind energy and aquaculture, or in avoiding overfishing in the most valuable fish areas. Our approach and analytical procedure can be replicated in the Baltic Sea or elsewhere provided that sufficient data exist.